2006
DOI: 10.1007/s00360-006-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Wheel-running activity and energy metabolism in relation to ambient temperature in mice selected for high wheel-running activity

Abstract: Wheel-running activity and energy metabolism in relation to ambient temperature in mice selected for high wheel-running activity Vaanholt, Lobke M.; Garland, Theodore; Daan, Serge; Visser, G. Henk; Garland Jr., Theodore; Heldmaier, G. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 29 publications
4
32
1
Order By: Relevance
“…As illustrated in Figs2 and 3, the energy expended on voluntary exercise can range from negligible to onethird of DEE in a mouse and two-thirds of DEE in a human in the Tour de France cycling race (Saris et al, 1989;Swallow et al, 2001;Vaanholt et al, 2007a;Vaanholt et al, 2007b;Rezende et al, 2009). In all cases, except perhaps during extreme human endurance activities, the energy expended in SPA is also appreciable.…”
Section: Dee and Its Componentsmentioning
confidence: 94%
See 2 more Smart Citations
“…As illustrated in Figs2 and 3, the energy expended on voluntary exercise can range from negligible to onethird of DEE in a mouse and two-thirds of DEE in a human in the Tour de France cycling race (Saris et al, 1989;Swallow et al, 2001;Vaanholt et al, 2007a;Vaanholt et al, 2007b;Rezende et al, 2009). In all cases, except perhaps during extreme human endurance activities, the energy expended in SPA is also appreciable.…”
Section: Dee and Its Componentsmentioning
confidence: 94%
“…They used the Tracmor tri-axial accelerometer, a device the size of a small pager that is worn on the waist. Their results provide evidence that older individuals compensate for increased exercise training by lowering their non-training activity during the remainder of the day, whereas no such compensation occurs in younger subjects, who show an increase in both accelerometer output (Saris et al, 1989) and for mice it represents the High Runner lines housed with wheel access Vaanholt et al, 2007a;Vaanholt et al, 2007b;Rezende et al, 2009). For the mice, some of the heat produced during wheel running is used for thermoregulation, thus reducing costs of thermoregulation per se.…”
Section: Summary Of Experimental Studies With Humansmentioning
confidence: 98%
See 1 more Smart Citation
“…Our mice were working at 3.7ϫBMR [assuming an estimated BMR of 0.61·kJ·g -1 ·d -1 in the Workload mice; based on the RMR measured at 22°C and earlier measurements in this strain of mice at thermoneutrality, 30°C (Vaanholt et al, 2007)], and thus close to their maximal sustainable rate. Studies investigating maximal sustainable rates imposed by other factors than exercise, such as cold exposure and lactation, have shown that mice are capable of even higher rates of energy expenditure.…”
Section: Body Temperature and Plasma Corticosteronementioning
confidence: 99%
“…One possible explanation for the lack of major alterations to the digestive track is that previous results Vaanholt et al, 2006;Swallow et al, 2001;Rezende et al, 2009) have demonstrated that the incremental cost of wheel running represents only a small portion of the total energy budgets of the mice. Koteja et al (1999) conclude: 'If wheel running in the selected lines continues to increase mainly by increases in velocity, then constraints related to energy acquisition are unlikely to be an important factor limiting further selective gain.'…”
Section: Controlmentioning
confidence: 99%